Robust Control for Nonlinear Time-Delay Systems - Hua, Changchun; Zhang, Liuliu; Guan, Xinping; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2018)
This book reports on the latest findings concerning nonlinear control theory and applications. It presents novel work on several kinds of commonly encountered nonlinear time-delay systems, including those whose nonlinear terms satisfy high-order polynomial form or general nonlinear form, those with nonlinear input or a triangular structure, and so on. As such, the book will be of interest to university researchers, R&D engineers and graduate students in the fields of control theory and control engineering who wish to learn about the core principles, methods, algorithms, and applications of nonlinear time-delay systems.
Keywords: Computer Engineering; System theory; Control and Systems Theory; Mathematical and Computational Engineering